2019
DOI: 10.1007/s00330-019-06090-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-detector CT imaging: impact of virtual tube current reduction and sparse sampling on detection of vertebral fractures

Abstract: Purpose To systematically evaluate the effects of virtual tube current reduction and sparse sampling on image quality and vertebral fracture diagnostics in multi-detector computed tomography (MDCT). Materials and methods In routine MDCT scans of 35 patients (80.0% females, 70.6 ± 14.2 years, 65.7% showing vertebral fractures), reduced radiation doses were retrospectively simulated by virtually lowering tube currents and applying sparse sampling, considering 50%, 25%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…However, it is time-consuming and labor-intensive to detect rib fractures in the "24 ribs" on hundreds of thin-slice CT images and missed rib fractures are not uncommon (1,7). Cho et al (1) reported that the rate of missed diagnosis of rib fracture on initial CT images reached 20.7%, significantly higher than those of the thoracic vertebrae or sternum (nearly 100% sensitivity) (8,9), which could lead to poor patient prognosis or adverse medicolegal disputes (10). Therefore, it is necessary to improve the accuracy of clinical diagnosis and reduce the rate of missed diagnoses.…”
Section: Dataset and Classification Criteriamentioning
confidence: 99%
“…However, it is time-consuming and labor-intensive to detect rib fractures in the "24 ribs" on hundreds of thin-slice CT images and missed rib fractures are not uncommon (1,7). Cho et al (1) reported that the rate of missed diagnosis of rib fracture on initial CT images reached 20.7%, significantly higher than those of the thoracic vertebrae or sternum (nearly 100% sensitivity) (8,9), which could lead to poor patient prognosis or adverse medicolegal disputes (10). Therefore, it is necessary to improve the accuracy of clinical diagnosis and reduce the rate of missed diagnoses.…”
Section: Dataset and Classification Criteriamentioning
confidence: 99%
“…Additionally, images with up to 50% reductions in radiation dose through sparse sampling can be used for finite element (FE)-based predictions of femoral failure load [35]. Sufficient image quality and diagnostic accuracy for detection of vertebral fractures could be achieved with 50% of original projections, while, on the contrary, MDCT with 50% lowered tube currents yielded inferior results [28]. Concerning the degenerative spine, the present study suggests that both sparse sampling and virtual reductions of tube current have potential for dose reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Initial preprocessing of imaging data used a total-variation method for the projection data to reduce image noise (λ = 0.01, n = 50) [24,25]. By the use of a simulation algorithm based on raw imaging data, we generated MDCT scans with virtually lowered tube currents in a stepwise fashion [26][27][28][29][30][31]. The approach for simulations of LD MDCT has been validated previously [31].…”
Section: Tube Current Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, this study achieved lowering of radiation exposure by reductions of tube current in combination with IMR, but did not evaluate other modern approaches to limit radiation exposure, such as sparse sampling. The technique of sparse sampling has shown high potential for even more drastic dose reductions with largely preserved image quality at the spine when compared to decreases in tube current 27,28 ; however, this has not yet been explicitly confirmed for MDCT scanning for planning purposes of neuroradiological interventions. While standard, commercially available MDCT scanners are not yet capable of using sparse sampling, first prototypes have already been constructed successfully 29,30 .…”
Section: R1 R2mentioning
confidence: 99%